Flow field analysis of grooved surfaces - Bayraktar, S.; Tekercioglu, R.; Dincel, A. T. (SPRINGER, 2019)
In the present study, two-dimensional turbulent flow over rectangular and octagonal grooves in a channel is analyzed numerically. Investigations are performed for two different Reynolds numbers, Re = 615 and 1230 in terms of velocity and temperature field. It is found that heat transfer increases with increasing Re number and using rectangular groove provides higher heat transfer than using the octagonal one. In comparison with rectangular groove, the octagonal one decreases the velocity of the incoming fluid and causes forming only one recirculation bubble in large size, while a secondary bubble occurs inside the rectangular one in addition to the primary bubble.
Keywords: Groove; Turbulence; Computational fluid dynamics (CFD); Heat transfer; ENHANCEMENT; CHANNEL; Environmental Sciences & Ecology